2006
DOI: 10.1016/j.molcel.2006.07.006
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: L-Type Ca2+ Channel Facilitation Mediated by Phosphorylation of the β Subunit by CaMKII

Abstract: L-type Ca(2+) channels (LTCCs) are major entry points for Ca(2+) in many cells. Ca(2+)/calmodulin-dependent protein kinase II (CaMKII) is associated with cardiac LTCC complexes and increases channel open probability (P(O)) to dynamically increase Ca(2+) current (I(Ca)) and augment cellular Ca(2+) signaling by a process called facilitation. However, the critical molecular mechanisms for CaMKII localization to LTCCs and I(Ca) facilitation in cardiomyocytes have not been defined. We show CaMKII binds to the LTCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
207
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(212 citation statements)
references
References 58 publications
4
207
0
1
Order By: Relevance
“…Whereas numerous studies described cloning of Ca 2ϩ channel subunits and Ca 2ϩ channel composition in the human, guinea pig, and rat heart (5,7,25,29,39,40,41) the molecular "make-up" of the mouse cardiac LTCC is much less defined, although several mouse lines have been created with Ca 2ϩ channel subunit transgenes as preclinical models for heart diseases (22,23,24,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas numerous studies described cloning of Ca 2ϩ channel subunits and Ca 2ϩ channel composition in the human, guinea pig, and rat heart (5,7,25,29,39,40,41) the molecular "make-up" of the mouse cardiac LTCC is much less defined, although several mouse lines have been created with Ca 2ϩ channel subunit transgenes as preclinical models for heart diseases (22,23,24,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Recent mouse models (e.g. 22,23,24) carrying a rat CaV␤2 splice variant ("rat CaV␤2a") (25) expressed in rat and rabbit brain (26), but not in rabbit heart (26), have only escalated this requirement, because it has never been shown that the mouse orthologue of this variant is endogenously expressed in the mouse heart. So far, five CaV␤2 variants varying only in the V1 domain have been identified from different species (25,27,28) and in human heart these variants have been obtained mainly by RT-PCR approaches (29,30).…”
mentioning
confidence: 99%
“…In the heart, CaMKII has been implicated in excitation-contraction (EC) coupling, gene transcription, and apoptosis (5,17). Many substrates involved in EC coupling such as phospholamban (PLB), the ryanodine receptor (RyR) and the L-type Ca 2ϩ channel (LTCC) have been reported (17)(18)(19)(20)(21)(22). We have also demonstrated that CaMKII isoforms associate specifically with histone deacetylase 4 (HDAC4), a transcriptional repressor (23) that, when phosphorylated, dissociates from the MEF2 transcription factor and translocates from the nucleus to the cytoplasm through its association with the 14-3-3 chaperone protein (18).…”
mentioning
confidence: 99%
“…A growing body of evidence has demonstrated that CaMKII can also be activated by ROS 21, 22, 23, 24. Once activated, CaMKII can phosphorylate a wide range of key Ca 2+ and Na + regulatory proteins such as LCCs,25, 26, 27, 28 RyRs,29, 30, 31, 32, 33, 34, 35 phosphalamban,29, 34, 36 and Na + channels 37, 38. Importantly, Xie et al39 showed that H 2 O 2 perfusion–induced oxidative CaMKII activation leads to afterdepolarizations in isolated rabbit cardiomyocytes, likely by phosphorylation of Na + channels and LCCs.…”
Section: Introductionmentioning
confidence: 99%